Gap between real-world data and clinical research within hospitals in China: a qualitative study. Issue 12 (29th December 2020) - Jin, Feifei; Yao, Chen; Yan, Xiaoyan; Dong, Chongya; Lai, Junkai; Li, Li; Wang, Bin; Tan, Yao; Zhu, Sainan
Abstract : Objective: To investigate the gap between real-world data and clinical research initiated by doctors in China, explore the potential reasons for this gap and collect different stakeholders' suggestions. Design: This qualitative study involved three types of hospital personnel based on three interview outlines. The data analysis was performed using the constructivist grounded theory analysis process. Setting: Six tertiary hospitals (three general hospitals and three specialised hospitals) in Beijing, China, were included. Participants: In total, 42 doctors from 12 departments, 5 information technology managers and 4 clinical managers were interviewed through stratified purposive sampling. Results: Electronic medical record data cannot be directly downloaded into clinical research files, which is a major problem in China. The lack of data interoperability, unstructured electronic medical record data and concerns regarding data security create a gap between real-world data and research data. Updating hospital information systems, promoting data standards and establishing an independent clinical research platform may be feasible suggestions for solving the current problems. Conclusions: Determining the causes of gaps and targeted solutions could contribute to the development of clinical research in China. This research suggests that updating the hospital information system, promoting data standards and establishing a clinical research platform could promote the use of real-world data in the future.